Effect of embedment depth of piles on response of three storeyed building frame incorporating non-linear behaviour of soil - Rasal, S.A.; Chore, H.S.; Sawant, V.A. (Journal of Structural Engineering, 2024)
The study deals with mathematical modeling of a typical three storeyed building frame supported by a pile group of four piles (2×2) embedded in soft marine clay, a cohesive type of soil mass, using three dimensional finite element analysis. For the purpose of modeling, the elements such as beams, slabs and columns, of the superstructure frame; and that of the pile foundation such as pile and pile cap are descretized using twenty noded isoparametric continuum elements. The interface between the pile and the soil is idealized using sixteen node isoparametric surface element. The soil elements are modeled using eight nodes, nine nodes and twelve node continuum elements. The present study considers the linear elastic behaviour of the elements of superstructure and substructure (i.e., foundation); and the soil is assumed to behave non-linear. The parametric study is carried out for studying the effect of soil- structure interaction on response of the frame by resorting to the sub-structure approach. The frame is analyzed initially without considering the effect of the foundation (non-interaction analysis) and then, the pile foundation is evaluated independently to obtain the equivalent stiffness; and these values are used in the interaction analysis. The embedment depth ratio is varied to evaluate its effect on the interactive behaviour of frame in the context pile spacing of 2D. The response of the frame included the horizontal displacement at the level of each storey, shear force in beams, axial force in columns along with the bending moments in beams and columns. The effect of the soil- structure interaction is observed to be significant for the configuration of the pile groups.